The Effect Of Additing Centella Asiatica L. Urban Leaves on the Moisture Content And Acceptability Of Centella Asiatica Sticks - Frenky Arif Budiman; Suprihartini, Cucuk; Wulandari, Catur; Suryaningputri, Rizqi Enjang (Universitas Nahdlatul Ulama Surabaya, 2024)
Pegagan (Centella Asiatica L. Urban) is a plant that belongs to the Umbelliferae or Apiaceae tribe. It is an herbal plant that grows on the ground, with a wide distribution area, especially in the tropics and subtropics. Currently, there is a scarcity of innovations for healthy and nutritious sticks, making it essential to explore new avenues in product development. Sticks are widelypopularamong people of all ages, from teenagers to adults. This study aims to analyze the moisture content and acceptability of gotu kola leaves sticks. The study employe a Completely Randomized Design (RAL) with one control and three treatments, namely 4%, 6% and 8%. Organoleptic tests and water content tests were cconducted on June 15, 2022, at the Chemical Laboratory of the Karya Husada Nutrition Academy, Kediri, Indonesia. The study results revealed a significance level of <0.05, indicating no difference in the acceptability of the color, aroma, texture and taste of pegagan leaves sticks. In the color acceptability test, 100% of panelists most favored sticks P1 and P2., in the aroma stick acceptance test the panelists most liked sticks P1 and P2 by 100%, For stick texture acceptance, 100% of panelists favored sticks P2., In the stickiness test, the preferred sticks weres P1 by 100%. The llowestt water content, with the addition of pegagan leaves, was found in treatment 1 with a 4% addition of pegagan leaves at 2.63%. further research is needed to explore the antioxidant content and the expiration of pegagan sticks.